Characteristics of and management strategies for 54 suicidal inpatients in a general hospital - Tan Rong; Hu De-Ying; Han Yan-Hong; Liu Yi-Lan; Ding Xiao-Ping; Wang Shu-Jie; Xu Ke (Sciendo, 2018)
The aim of this study was to explore the characteristics of and preventive management strategies for suicidal inpatients in a general hospital.